Clinical spectrum associated with aquaporin-4 antibodies (NMO-IgG) - Y. Blanco; K. Hankiewicz; S. Llufriu; L. Sabater; F. Graus; A. Saiz (Neurología (English Edition), 2010)
Introduction: The description of a highly sensitive and specific biomarker for neuromyelitis optica (NMO-IgG/aquaporin-4 antibody) extended the clinical spectrum of NMO to limited forms such as optic neuritis (ON) and longitudinally extensive myelitis (LEM). Objective: To asses the sensitivity and specificity of our assay, and to describe the clinical characteristics of the patients who were tested for NMO-IgG. Methods: NMO-IgG was analysed by immunohistochemistry and confirmed by assay on HEK cells transfected with aquaporin-4. The clinical information was obtained from forms filled in by the referring neurologists. Results: A total of 580 samples from 518 patients were analysed from November 2005 to September 2008. Clinical information was available from 358 (68%) patients. All 33 (100%) positive cases were followed up. Twenty-eight of the 43 (65%) patients diagnosed with NMO by the revised criteria of 2006 were positive; the sensitivity was 62.5% when applying the same criteria, but discounting the criterion of NMO-IgG status, or 57% when applying the criteria of 1999. NMO-IgG was detected in 3 (13%) of the recurrent LEM and 2 (4%) of the recurrent ON. NMO-IgG was not detected in the remaining patients (96 with a final diagnosis of multiple sclerosis; 80 with myelitis; 28 with non-recurrent ON; and 33 other diagnosis). Conclusions: No false positive cases were found in this large and non-selected study. NMO-IgG positive cases were mostly associated with NMO, and only in a low percentage with recurrent ON or LEM. Resumen: Introducción: Los anticuerpos IgG-NMO se han demostrado sensibles y específicos para el diagnóstico de neuromielitis óptica (NMO) y han permitido ampliar el espectro clínico a formas limitadas como neuritis óptica (NO) o mielitis longitudinalmente extensas (MLE). Objetivo: Evaluar la sensibilidad y la especificidad de nuestra técnica y describir las características de los pacientes para los que se solicita dicha determinación. Métodos: Los anticuerpos IgG-NMO se analizaron mediante inmunohistoquímica y se confirmaron sobre células HEK transfectadas con acuaporina 4. La información clínica se obtuvo mediante un cuestionario rellenado por el neurólogo remitente de la muestra. Resultados: Desde noviembre de 2005 a septiembre de 2008 se analizaron 580 muestras de 518 pacientes. Se obtuvo información de 358 (68%) pacientes. El seguimiento en los 33 casos positivos fue del 100%. De los 43 pacientes diagnosticados de NMO por los criterios de 2006, 28 (65%) eran positivos; la sensibilidad fue del 62,5% si se aplicaban estos criterios eliminando el resultado de IgG-NMO y del 57% aplicando los criterios de 1999, que tampoco incluyen los IgG-NMO. Se detectaron IgG-NMO en 3 (13%) de las MLE recurrentes y 2 (4%) de las NO recurrentes. No se detectaron IgG-NMO en el resto de los pacientes evaluados (96 finalmente diagnosticados de esclerosis múltiple; 80 mielitis; 28 NO no recurrentes; 33 con otros diagnósticos). Conclusiones: En este estudio no seleccionado y tan amplio, no se han detectado falsos positivos. Los casos positivos se asocian mayoritariamente con NMO y sólo en un pequeño porcentaje con NO o MLE recurrente. Keywords: Neuromyelitis optica, Multiple sclerosis, NMO-IgG, Aquaporin-4, Transverse myelitis, Optic neuritis, Palabras clave: Neuromielitis óptica, Esclerosis múltiple, IgG-NMO, Acuaporina 4, Mielitis transversa, Neuritis óptica